2004
DOI: 10.1063/1.1760514
|View full text |Cite
|
Sign up to set email alerts
|

Chain elongation suppression of cyclic block copolymers in lamellar microphase-separated bulk

Abstract: Chain elongation suppression of cyclic block copolymers in microphase-separated bulk was determined quantitatively. Solvent-cast and annealed films are confirmed to show alternating lamellar structure and their microdomain spacing D increases with increasing total molecular weight M according to the relationship D proportional, variant M0.59, which agrees quite consistently with the theoretically predicted power law, i.e., D proportional, variant M3/5. This result is in contrast to the well-established issue f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
32
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 30 publications
0
32
0
Order By: Relevance
“…The difference between cyclic and linear polymers, in terms of molecular structure, is only the presence or the absence of chain ends. However, this small difference leads to various kinds of different physical properties, such as chain dimension in solution and bulk, 5,21,[27][28][29][30][31] glass transition temperatures, [32][33][34][35] viscoelasticity, 36,37 diffusion, [38][39][40][41][42][43] microphase-separated structures 44 and crystallization [45][46][47] among others. Hence, cyclic polymers are one of the ideal model polymers to use for understanding the effect of topology on the thermodynamics and molecular motion of polymers.…”
Section: Introductionmentioning
confidence: 99%
“…The difference between cyclic and linear polymers, in terms of molecular structure, is only the presence or the absence of chain ends. However, this small difference leads to various kinds of different physical properties, such as chain dimension in solution and bulk, 5,21,[27][28][29][30][31] glass transition temperatures, [32][33][34][35] viscoelasticity, 36,37 diffusion, [38][39][40][41][42][43] microphase-separated structures 44 and crystallization [45][46][47] among others. Hence, cyclic polymers are one of the ideal model polymers to use for understanding the effect of topology on the thermodynamics and molecular motion of polymers.…”
Section: Introductionmentioning
confidence: 99%
“…TEM observations were carried out by adopting the same manner reported previously. 22 Figure 2 shows typical TEM images of the sample I 1.0 S 1.0 P 1.3 . It has been confirmed that three polymer chains branched at one junction point all show cylinder-based structure.…”
mentioning
confidence: 99%
“…Herein, the solid and hollow symbols (triangle, circle, and pentagram) represent the rod blocks played as the minor or major moiety in micelle, cylinder, and gyroid phases, respectively. Similar to the case of coil-coil diblock copolymers (no matter linear or cyclic case), 21,25,34,35 with varying block composition f, the morphology is transited from micelle to cylinder to lamellae, and then inversely from lamellar to cylindrical to micellar phase, respectively. There are some intermediate structures between lamellar and cylindrical phase regions, such as gyroid (G) and perforated lamellae (PL), which are observed commonly in experimental studies.…”
Section: Resultsmentioning
confidence: 82%